Muhammad Abid al-Jabiri's Intellectual Contribution to Moderating Tradition and Modernity in Moroccan Islamic Education Reform - Tamami; Helmiati; Nazir; abdelmounaim (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This study explores the contribution of Muhammad Abid al-Jabiri's thought to the reform of Islamic education in Morocco, inspiring a balanced integration of tradition and modernity. This research is significant given the challenges of globalization and radicalism that Islamic education systems experience. Previous studies have primarily focused on historical and structural aspects and have yet to delve into the impact of al-Jabiri's ideas on policies and curricula. This research uses a qualitative approach based on content analysis to examine historical documents, educational policies, and al-Jabiri's works, such as Naqd al-Aql al-Arabi, to analyze the influence of his ideas on integrating religious and modern scientific knowledge. The analysis evaluates the transformation of Islamic education across three significant periods: pre-colonial, colonial, and post-colonial. The findings reveal that al-Jabiri's thought has successfully inspired curricula rooted in values of rationality and moderation, which are relevant for addressing globalization challenges without losing Islamic identity. These reforms promote inclusive and globally competitive education. The study recommends an integrative education model based on moderation as a solution to create an inclusive and tolerant society. Further research is needed to understand the long-term impacts of these reforms on social development and Islamic identity in the modern era.